Symmetric and Asymmetric Effects of Attitude and Satisfaction on Sustainable Business Growth - Sheikh Ashiqurrahman Prince; Md Mominur Rahman; Sayed Azharul Islam (Journal of Risk Analysis and Crisis Response (JRACR), 2024)
Microfinance plays a crucial role in fostering economic development, especially in underserved and impoverished communities. Using stimulus-organism response (SOR) theory, the study investigates how microfinance, cost of loan, and individual funding and support affect borrowers' business attitudes and sustainable business growth, as well as the impact of satisfaction with these sources. The study collected 845 data points from the Khulan division of Bangladesh using a convenient sampling technique and analyzed them with Smrt Pls 4 and fsQCA 3 software. The results indicated that microfinance, cost of loan individual finding, and support significantly affect borrowers’ business attitudes which in turn has a positive effect on sustainable business growth. The findings further show that apart from the relationship between microbusiness and business attitudes, business satisfaction does not moderate the relationships between cost of loan and business satisfaction as well as individual finding and support and business satisfaction. The study suggests insightful recommendations for academics, MFIs, and policymakers for poverty reduction through ensuring sustainable business conducted by microfinance. This study introduces two new concepts i.e., individual funding and support and business satisfaction as well as a new theory i.e., SOR in microfinance research, extending the theory's applicability, and research scope, and providing new suggestions for further research.